Impact of apical foreshortening on deformation measurements: a report from the EACVI-ASE Strain Standardization Task Force. (30th July 2019) - Ünlü, Serkan; Duchenne, Jürgen; Mirea, Oana; Pagourelias, Efstathios D; Bézy, Stéphanie; Cvijic, Marta; Beela, Ahmed Salem; Thomas, James D; Badano, Luigi P; Voigt, Jens-Uwe; ,
Abstract: Aims: Foreshortening of apical views is a common problem in echocardiography. It results in an abnormally thick false apex and a shortened left ventricular (LV) long axis. We sought to evaluate the impact of foreshortened (FS) on LV ejection fraction (LVEF) and layer-specific 2D speckle tracking based segmental (S) and global (G) longitudinal strain (LS) measurements. Methods and results: We examined 72 participants using a GE Vivid E9 system. FS apical views were collected from an imaging window one rib-space higher than the optimal images. Ejection fraction as well as layer-specific GLS and SLS measurements were analysed by GE EchoPAC v201 and TomTec Image Arena 4.6 and compared between optimal and FS images. On average, LV long axis was 10% shorter in FS images than in optimal images. FS induced a relative change in LVEF of 3.3% and 6.9% for GE and TomTec, respectively (both, P < 0.001). Endocardial GLS was 9.0% higher with GE and 23.2% with TomTec ( P < 0.001). Midwall GLS measurements were less affected (7.8% for GE and 14.1% for TomTec, respectively, both P < 0.001). Segmental strain analysis revealed that the mid-ventricular and apical segments were more affected by foreshortening, and endocardial measurements were more affected than midwall. Conclusion: Optimal image geometry is crucial for accurate LV function assessment. Foreshorhening of apical views has a substantial impact on longitudinal strain measurements, predominantly in the apex and in the endocardial layer. Our data suggest that measuring midwall strain might therefore be the more robust approach for clinical routine use.